Dynamics of turnover of sugar-lowering drugs in the retail segment of the pharmaceutical market from 2020 to 2024 - D. V. Kurkin; E. V. Makarova; V. I. Zvereva; A. R. Makarova; D. A. Bakulin; O. V. Marincheva; Yu. V. Gorbunova; Yu. A. Kolosov; I. S. Krysanov; K. N. Koryanova; D. A. Galkina; N. A. Osadchenko; et al. (Фармация и фармакология (Пятигорск), 2025)
A significant part of patients with diabetes purchase sugar-lowering drugs (SLDs) on their own in retail pharmacy chains, and the market trends they generate represent an urgent area for this study.The aim. To study the turnover of hypoglycemic drugs, including insulins, in the commercial sector of the pharmaceutical market of the Russian Federation (RF) for 2020–2024.Materials and methods. The data presented in this article is based on a periodic retail audit conducted by the biotech company IQVIA. The period of 5 years (2020–2024) was covered. Data collection covered 33,613 commercial pharmacies in all regions of the RF (about 43% of pharmacies).Results. In the period from 2020 to 2023, a relatively stable increase in the volume of SLDs purchases was revealed, with small fluctuations, while in 2024 a significant leap in consumption was recorded, both in quantitative (packages) and in value (rubles) terms. During the entire monitoring period, the total volume of SLDs and insulin purchases in the retail market segment increased by more than 1.2 times, from 41.98 million packages in 2020 to 51.70 million in 2024. At the same time, the total procurement budget (at wholesale prices) increased by more than 2 times — from 19.40 to 41.57 billion rubles. The average price per package has also increased significantly, from 462 rubles in 2020 to 923 rubles in 2024, an increase of 1.7 times, reflecting significant inflation in the commercial pharmaceutical sector. In general, the Russian pharmaceutical market offers all variants of modern innovative hypoglycemic drugs (dipeptidyl peptidase-4 inhibitors [iDPP4], sodium-glucose cotransporter 2 inhibitors [iSGLT2], glucagon-like peptide-1 receptor agonists [arGPP-1]), which, according to general trends, demonstrate a steady increase in turnover. Older and less effective sulfonylureas and their combinations with metformin still occupy a significant market share. arGPP-1 group showed the greatest growth in quantity (11 times) and value (5 times), mainly due to the entry of Russian semaglutide analogues into the market. Government measures and investments in import substitution have led to a significant increase in the share of Russian drugs in purchases. Despite the positive dynamics of Russian production, import substitution in the SLDs segment has not achieved complete success and accounts for less than half of the turnover of hypoglycemic drugs.Conclusion. The growth of SLDs consumption in the retail segment of the RF in 2020–2024 has been revealed, especially due to the innovative drugs arGPP-1 and iNGLT2. Despite maintaining the leading position of metformin, the consumption structure is shifting towards more expensive schemes. The increase in the total procurement budget and the average package price highlights the need to expand preferential security programs. Import substitution has increased significantly over the indicated period, however, the share of domestic drugs is still less than half of the turnover.